Gingival Thickness and Outcome of Periodontal Plastic Surgery Procedures: A Meta-regression Analysis. (July 2021) - Holtzman, L. Paternò; Blasi, G.; Rivera, E.; Herrero, F.; Downton, K.; Oates, T.
Objective: To evaluate the impact of soft tissue thickness (STT) on root coverage achieved with different periodontal plastic surgery procedures. Background: Gingival recession has been managed successfully through various surgical approaches, with great variability in outcomes. Anatomic characteristics of the recipient site and selected technique account in part for this variability. Gingival flap thickness is one of the most critical site-related characteristics. Methods: An electronic search was conducted on the major databases (PubMed, Embase, Web of Science). Human prospective studies with at least 6 mo of follow-up and with a numeric baseline measurement for gingival thickness were eligible. Only studies including nonsmoking patients were considered. Variables included surgical approach, participant characteristics, local anatomic factors, and follow-up time. Primary outcome was mean percentage root coverage (%RC) achieved, and complete root coverage was a secondary outcome. Results: A total of 42 studies were included (35 randomized controlled trials, 5 case series, 1 prospective cohort study, and 1 controlled clinical trial). Across studies, the pooled %RC was 81.9% (95% CI, 79.1% to 84.7%). The %RC was not significantly associated ( P = 0.267) with baseline soft tissue thickness; however there was a significant ( P = 0.031) inverse relationship between STT and %RC after 12-mo follow-up. Subgroup analysis showed that for no graft, there was a significant ( P = 0.025) positive relationship between STT and %RC with the exclusion of the single outlier study based on STT. Conclusions: STT plays a limited role in predicting root coverage across all approaches; when flaps are performed with no graft, the effect of STT is most critical. The length of time following surgery appears to influence outcomes, with 12-mo follow-up offering greater insight. Knowledge Transfer Statement: The results of this study can suggest to clinicians which periodontal plastic surgery technique to employ when treating challenging cases. In particular, it can be helpful when selecting the treatment approach to treat thin phenotype sites. This study could help clinicians provide a more appropriate treatment decision in such cases.